SUMBER IDE SIPUT GONGGONG DALAM PENCIPTAAN BUSANA PESTA MUSLIM - Destivana Eka Murti; Titin Prihatini (Jurnal Socia Akademika, 2021)
This study aims to create Muslim party fashion with the idea of gonggong snails and to know the results of respondents to the fashion made. This research is descriptive. Data collection techniques used through questionnaires and documentation are used to measure the response of adolescents to Muslim party fashion made. Data analysis techniques using descriptive data analysis. From the results of the research obtained Muslim party fashion with details, namely: in the form of Muslim dresses made of Gonggong batik fabric and bridal satin fabric. Batik gonggong blends dark brown and cream colour, fine-textured and luxurious impression, combined with a golden brown satin bridal cloth whose texture is shiny and a bit thick and stiff to make peplum that resembles a snail shell, gonggong so it is suitable for Muslim party fashion. In addition, the addition of a belt decoration sprinkled with beads and sequins with the source of the idea of snail bark looks suitable. The results of the poll analysis of respondents stated 95% there is design conformity, 100% stated there is a conformity of colour, and 95% that states look good for the resulting party dress